Reinventing the passive design framework in the tropics: the experience of green rating systems and passive strategies - Jahn Kassim, Puteri Shireen; Zainal Abidin, Siti Norzaini; Mohd Ariffin, Noor Aziah (2019)
The rise of green building rating systems has spurred significant changes to the design, specification and construction processes and specifications. Yet in the tropical context, the key issues - given the challenges of the hot climate – remain as to how to integrate, reward and prioritise, passive design initiatives, processes and efforts by the design team which occur earlier in design processes; including the optimisation for climate in architectural design. The filtration of heat gain, natural light and ventilation, is of crucial issue to both energy and comfort criteria. The paper highlights how three projects encounter these strategies and its rewards and achievements; within the present assessment systems. Tropical cities and its urban context present a challenging climate due to rising urban heat island effects and the emerging range of typologies in its urbanising region; such as schools, hotels, highway rest enters, and airconditioned buildings, within which there is no precedent and which still utilise passive systems such as natural ventilation and controlled daylight to save energy. The projects discussed in the paper refers to how different green building rating systems integrate the strategic role of passive design to induce changes in architectural form, envelope and reduce costs of mechanical and electrical systems and specifications towards targets of energy saving. As one of the cost-effective strategies in green building, passive-related decisions made early during the design process; including performance-based and optimisation processes can reduce energy long-term without the associated high capital costs. Daylight, ventilation, heat gain with landscape; are coupled with strategic simulation inputs highlight how the design development process – spurred by green systems –can encourage more integrated actions and decisions. Yet such strategies must be rewarded accordingly by the current green building rating systems and efforts to continuously revise, reframe and revamp the framework of supporting and rewarding bioclimatic- passive design must respond to its increasingly importance in controlling costs and rise of massive urbanisation in Asia to fully relate to changing scenarios of low-energy design and architecture.